Crimes Against Humanity and International Legal Responses to the Rohingya Crisis: A Normative Analysis of State Responsibility and Global Judicial Mechanisms - Dede Al Mustaqim; Zahra Aulia Suwandi; Huda (Journal Discrimination and Injustice, 2025)
The humanitarian crisis experienced by the Rohingya in Myanmar represents one of the gravest human rights violations of the twenty-first century. This study aims to identify the forms of crimes against humanity committed against the Rohingya, analyze the Myanmar government’s actions through the lens of international law, and assess the role of international judicial bodies in enforcing accountability. Employing a normative juridical method with a literature-based approach, this research draws on international legal instruments including the Rome Statute, UN Fact-Finding Mission reports, and global human rights documents supported by relevant theoretical frameworks in international criminal law. The findings reveal that mass killings, rape, forced deportation, and the systematic burning of villages constitute crimes against humanity under Article 7 of the Rome Statute and are reinforced by discriminatory state policies such as the 1982 Citizenship Law. Furthermore, the study highlights the critical roles of the International Court of Justice (ICJ) in adjudicating genocide allegations and the International Criminal Court (ICC) in pursuing preliminary investigations. This research concludes that the Rohingya crisis constitutes an international crime requiring collective intervention and legal enforcement. It recommends strengthening global judicial cooperation, enhancing accountability mechanisms, and ensuring sustained international oversight to protect victims and prevent recurrence.